ZIKA VIRUS AN EPIDEMIOLOGICAL PROFILE: BIBLIOGRAPHIC REVIEW - Silvana Araujo Cardoso, Francisca; Kennedy de Araújo Beserra, Walter; Macedo Esbell Gomes, Diane; Cristina Dourado de Souza, Lorena; Fernandes Pires Pereira De Almeida, Nádia; Carlos do Nascimento Lopes, João; Regina Alves De Oliveira, Lúcia; da Silva dos Santos, Odilamir; Jeanne Carvalho Nascimento, Sydia; Mota de Carvalho, Raimunda (Health and Society, 2022)
Known scientifically ZIKV, constituted in viruses when so enveloped in the unsegmented single RNA chain of the flaviviridae family and flavivirus genus then discovered and isolated in 1947 the Zika virus emerged in the Zika forest in Uganda in monkey-reso and discovered in humans in 1968. Its main means of transmission is by the Aedes Aegypti mosquito and also by sexual intercourse, blood contact, breast milk and amniotic fluid. In Brazil the zika virus was featured during the World Cup in 2014 because many foreigners are from different nations. Treatment is symptomatic means that there is no specific treatment just to relieve symptoms and protect yourself from mosquito bites so it does not carry the disease to other people. In order to carry out this bibliographic review, the Scienc Direct, SciELO, Medline, Capes Periodicals, Google Scholar and Brazilian Ministry of Health databases were used, being considered articles in the Portuguese language according to the quality and relevance of the proposed theme of this review. This work did not pretend to bring something new but to highlight the great health problem that this pathology can cause to the human being and in all its biogenesis.